Ontology Based Development of Domain Specific Languages for Systems Engineering - Mezhuyev, Vitaliy (2014)
The new approach to development of Domain Specific Languages (DSL) for solving tasks of Systems Engineering (SE) is proposed. A DSL alphabet is defined on the base of an ontology of the SE domain as the set of its typical concepts. A DSL grammar on the base of Finite State Machine (FSM) formalism is defined, which allows to link the SE ontology with the different SE processes (specification of requirements, work planning, development, validation, standardisation etc.). A DSL is mapped with the set of mathematical methods, which allows to solve arising in the SE domains tasks. The approach on the sample of development of the DSL for specification of requirements is illustrated.